2015
DOI: 10.11604/pamj.2015.20.156.4571
|View full text |Cite
|
Sign up to set email alerts
|

Séroprévalence et facteurs associés au VIH et aux hépatites virales B et C dans la ville de Bafoussam au Cameroun

Abstract: IntroductionL'objectif de ce travail était de déterminer la séroprévalence et les facteurs associés au VIH et aux hépatites virales B et C dans la ville de Bafoussam au Cameroun.MéthodesIl s'agissait d'une étude descriptive et analytique réalisée de février 2012 à Juin 2012 dans la ville de Bafoussam au Cameroun. Pour cette étude, nous avons obtenu une clairance éthique.RésultatsAu total, 982 personnes ont été dépistées pour le VIH et les hépatites virales B et C. Les femmes représentaient 56,3% des personnes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This result is higher than the 4.1% recorded by Mbopi-keou et al . [ 17 ] in a study conducted in Bafoussam, Cameroon. This disparity can be justified by the difference in the population studied, of which those in the present one were mostly students who are more likely to be vulnerable to unsafe sexual practices.…”
Section: Discussionmentioning
confidence: 99%
“…This result is higher than the 4.1% recorded by Mbopi-keou et al . [ 17 ] in a study conducted in Bafoussam, Cameroon. This disparity can be justified by the difference in the population studied, of which those in the present one were mostly students who are more likely to be vulnerable to unsafe sexual practices.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also found an association between HIV status and these diseases [15][16][17]. STIs play a major role in the sexual transmission of HIV.…”
Section: Discussionmentioning
confidence: 73%
“…HCVAb seroprevalence in Cameroon varies across regions and tribes within the same country. While some studies reported high HCVAb carriage: in the southern 12% [ 34 ], in the western 6.3% [ 35 ], numerous studies on the contrary revealed a relative much lower prevalence: 2.2% anti-HCV in the Northern [ 27 ], 0.6% in the eastern [ 36 ], 0.4% in the western [ 37 ], 4.8% in the Littoral Region [ 38 ], 1.44% in the center region [ 39 ]. Equally, various burden of anti-HCV antibodies have also been reported in community settings worldwide: 0.77% in Romania [ 40 ], 1.02% in Sudan [ 41 ], 1.2% in Madagascar [ 42 ], 2.4%in Iraq [ 43 ], 3.6% in India [ 44 ], 19.80% in Cairo [ 45 ].…”
Section: Discussionmentioning
confidence: 99%